Indonesian Interference in Students' Japanese Essays of SMK Penerbangan Cakra Nusantara School - Devi Ayu Andari, Putu (e-Journal of Linguistics, 2020)
This research discusses Indonesian language interference that occurs in Japanese essays written by SMK Penerbangan Cakra Nusantara students. This research aims to describe the types of interference found in the form of sentences in students' essays. This research used qualitative descriptive. The subject of this research are students of XII APP 1 class, meanwhile the object of this research are interference sentences in Japanese essays. The data was collected through note taking technique. The data was analysed using a theory proposed by Miles and Hubberman by performing data reduction, analysing data, and making conclusions. The results of this research are 1) the types of interference that occured based on linguistic aspects are morphological and syntactic interference; and 2) syntactic interference occured in three types of interference such as permutation of core constituents (I) and modifier (M), permutation of predicate (P) and object (O), and ommision of particles ( joshi ).